The effects of place of residence on tourist motivations: a revised case of the Urban Quadrangle of Minho - Mendes, Raquel (2013)
This study seeks to capture the underlying reasons for the travel decisions of residents of the Urban Quadrangle of Minho (composed of the municipalities of Barcelos, Braga, Guimarães, and Vila Nova de Famalicão). The aim of the research is three-fold. Firstly, the study identifies the push and pull motivational factors of residents of the Urban Quadrangle of Minho. Secondly, the study examines whether there are differences between the tourist motivations of residents of the four different municipalities of the Urban Quadrangle. Finally, the study investigates if there are any differences in the motivations of those who choose national and international destinations. The methodology comprises quantitative research based on questionnaires administered in 2012 to residents of the Urban Quadrangle of Minho. A principal component factor analysis is employed to identify six push and seven pull factors. The comparison of the mean scores of these factors across municipalities and across residents that choose national and international destinations reveals that the most valued and least valued factors are common to all four municipalities and both groups of residents (that choose national and international destinations).